2013
DOI: 10.1080/02687038.2013.770818
|View full text |Cite
|
Sign up to set email alerts
|

Turning the tide: Putting acute aphasia management back on the agenda through evidence-based practice

Abstract: Background: The role of speech pathologists working in the acute hospital setting has evolved away from service provision to people with aphasia and their families towards a stronger focus on dysphagia. Evidence-based practice (EBP) can be conceptualised as the integration of four streams of evidence: research-based clinical evidence, clinical expertise, patient preferences and values, and the practice context. EBP is an important tenet in current healthcare. However, it is not clear whether speech pathologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Most people are now familiar with the notion of evidence-based practice (EBP) and the seminal definition of Sackett et al, 50 which suggests that EBP occurs when external research evidence is applied with expertise and in the light of patient preferences; others have also emphasised the role of context in framing EBP. 51 Various barriers to the implementation of EBP have been identified including the time needed to search out research and, in particular, research that is relevant and appropriate to the particular context of an individual patient. 52 There is also a lack of research that attempts to advance our understanding of the process of integration of the three elements.…”
Section: Assumptions Underpinning An Evidence-based Frameworkmentioning
confidence: 99%
“…Most people are now familiar with the notion of evidence-based practice (EBP) and the seminal definition of Sackett et al, 50 which suggests that EBP occurs when external research evidence is applied with expertise and in the light of patient preferences; others have also emphasised the role of context in framing EBP. 51 Various barriers to the implementation of EBP have been identified including the time needed to search out research and, in particular, research that is relevant and appropriate to the particular context of an individual patient. 52 There is also a lack of research that attempts to advance our understanding of the process of integration of the three elements.…”
Section: Assumptions Underpinning An Evidence-based Frameworkmentioning
confidence: 99%
“…This is supported by a review of the literature which concluded that little is known about how speech pathologists understand, integrate and implement the different streams of evidence in EBP in the management of acute aphasia (Foster et al . ). In addition, we have little knowledge of the barriers and facilitators to achieving EBP in specific clinical contexts.…”
Section: Introductionmentioning
confidence: 97%
“…This chapter was published in the journal Aphasiology (Foster, Worrall, Rose, & O'Halloran, 2013). Using an evidence-based practice model, this chapter provides a description and evaluation of how the different streams of evidence contribute to the management of aphasia by speech pathologists in the acute hospital setting.…”
Section: Thesis Overviewmentioning
confidence: 99%
“…Firstly, because a review of the literature found that context -represented in both the country and the clinical setting in this research -is an important variable in the implementation of EBP (see Background section). Secondly, because research has revealed an evidence-practice gap in the provision of aphasia services in the acute hospital setting (Foster et al, 2013). In addition, participants with recent clinical experience were required given the nature of enquiry which required reflection upon and analysis of personal experiences.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation